2018
DOI: 10.2147/dddt.s178020
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of rosuvastatin efficacy in prevention of contrast-induced acute kidney injury

Abstract: BackgroundContrast-induced nephropathy (CIN) is a complication after the intravascular administration of a contrast medium injection. Previous studies have investigated statins as therapy for CIN due to its positive results in the prevention of contrast-induced acute kidney injury (CI-AKI). Nevertheless, the beneficial effects of rosuvastatin pretreatment in preventing CIN in patients with acute coronary syndromes still remain controversial. In this study, we performed a meta-analysis of randomized controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
(35 reference statements)
1
11
0
1
Order By: Relevance
“…A recent systematic evaluation showed that the risk of CA-AKI in high-risk patients, such as those with CKD or DM, can be reduced by short-term use of rosuvastatin before CM administration (OR: 0.53, 95% CI: 0.40 to 0.71, P < 0.0001) [91]. However, the efficacy of statins in the prevention and treatment of CA-AKI remains controversial [92].…”
Section: Treatmentmentioning
confidence: 99%
“…A recent systematic evaluation showed that the risk of CA-AKI in high-risk patients, such as those with CKD or DM, can be reduced by short-term use of rosuvastatin before CM administration (OR: 0.53, 95% CI: 0.40 to 0.71, P < 0.0001) [91]. However, the efficacy of statins in the prevention and treatment of CA-AKI remains controversial [92].…”
Section: Treatmentmentioning
confidence: 99%
“…Although the risk of developing CIN is low in patients with good renal status, it is remarkably higher in those with conditions such as diabetes mellitus or chronic kidney disorder [4,28]. Many clinical trials and meta-analysis have con rmed that the incidence of CIN is increasingly common among patients with diabetes mellitus [29]. Given the adverse outcome of this issue, every effort should be done to decrease the incidence of CIN among those high-risk patients.…”
Section: Resultsmentioning
confidence: 99%
“…Still, being a patient with diabetes will have a constant risk for ACS and its complications and fatality if compared with others, which their risks decreased over time with introduction of revascularization procedures [ 32 ]. Loading dose of statins prerevascularization was found to be associated with lower risk of CI-AKI and complications [ 33 , 34 ]. In our cohort, the use of statins was also associated with lower rate for events and revascularization.…”
Section: Discussionmentioning
confidence: 99%